Adult food borne botulism in Australia: The only 2 cases from the last 15 years. (July 2017) - Ramachandran, Prashanth; Chan, Eddie; Poon, Michael; Tu, Hans T.H.; Davis, Jennifer M.; Eisen, Damon; Marriott, Mark
Highlights: Consider botulism in a patient with weakness, ptosis, internal and external ophthalmoplegia and autonomic features. In contrast to acute neuropathies (e.g. Miller Fisher syndrome), the reflexes are usually preserved. Toxin serotype may predict clinical course and severity. An anti-toxin is available and should be given early and rigorous case follow-up is vital in food borne outbreaks. With good supportive care, the prognosis is excellent but recovery is often protracted over many months.